Worm Causing Diabetes - Akanksha Singh; Ajay Chauhan; Amrinder Singh; Parul Goyal; Piyush Jain (Indian Journal of Medical Specialities)
Hydatid disease or echinococcosis is one of the oldest known zoonotic diseases. Although known to be found in liver and lungs, these cysts are rarely found in the pancreas. We report a patient who not only had hydatid cyst in the pancreas but also pancreatitis and subsequently diabetes because of it.